2021
DOI: 10.6007/ijarbss/v11-i4/9816
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Promotion and Waqf Knowledge toward Cash Waqf Awareness in Pahang Region

Abstract: The notion that waqf only involves permanent property such as graveyards, mosques and buildings is well established among the community. However, developments during the implementation of wakaf have given birth to new mechanisms involving the use of nonpermanent property such as money better known as cash wakaf. Cash waqf is a waqf mechanism that raises waqf funds and then converts them into permanent property. However, the existence of this cash wakaf is still in doubt among the community because the use of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 10 publications
0
14
0
1
Order By: Relevance
“…The importance of knowledge in influencing people's intentions has been validated by Hassan et al (2021), which found that knowledge has a strong and positive association with waqf participation. This was corroborated by Kadir et al (2018), which mentioned that knowledge has a major influence on the desire to donate to waqf.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of knowledge in influencing people's intentions has been validated by Hassan et al (2021), which found that knowledge has a strong and positive association with waqf participation. This was corroborated by Kadir et al (2018), which mentioned that knowledge has a major influence on the desire to donate to waqf.…”
Section: Discussionmentioning
confidence: 99%
“…This is followed by promotion, income and finally, social culture (Ahmad, 2019). Another study which use a different method, Smart PLS (Structural Equation Modelling), stated that factors of knowledge and promotion still showed significant and positive relations toward providing awareness and understanding of this cash endowment (Hassan et al, 2021). Nevertheless, some studies showed a contrasting result, whereby respondents were indifferent about the factor that promotion influenced their awareness on cash waqf (Adayemi et al, 2016;Iqbal et al, 2019;Khadijah & Nazri, 2020).…”
Section: Literature Review Cash Waqf Awarenessmentioning
confidence: 99%
“…Multiple regression model has been used in many studies to test the significance of relationship between independent variables (attitude, subjective norms, perceived behavior control) with dependent variable (intention to participate in cash waqf) in studies conducted by (Khadijah & Nazri, 2020;Yusoff et al, 2018). There were also researchers who used the Partial Least Square (PLS) -Structural Equation Modelling (SEM) for similar research (Ismail and Maryanti, 2022;Kasri and Chaerunnisa, 2022;Hassan et al, 2021;Purnamasari et al, 2021;Kasri and Kamil, 2021) Despite those two common methods, we can use the logistic regression model or also known as logit model. The dependent variable in this study is the intention of cash waqf where it is measured dichotomously with 1 for those who have the intention to perform cash waqf and 0 for those who do not have the intention to perform cash waqf.…”
Section: Estimationmentioning
confidence: 99%
“…Thus, waqf remains a unique concept in that it has durable, unchallengeable and irrevocable features (Adeyemi et al. , 2016; Hassan et al. , 2021; Shukor et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although there are few studies on Muslims' awareness and perception of waqf activities (Adeyemi et al. , 2016; Hassan et al. , 2021; Ismawati and Anwar, 2019; Shukor et al.…”
Section: Introductionmentioning
confidence: 99%